Analisis Kemandirian Anak Usia Dini di Kelas B di TK Negeri Pembina Kota Gorontalo - Davina S Maladjai; Dwi A Nggai; Indriyati T Husain; Lala Anoez; Fiola Indah Putri Pratama (Inovasi Pendidikan dan Anak Usia Dini, 2025)
The importance of children's independence, one of the important factors in children's growth and development is independence. This research aims to determine the importance of developing independence in early childhood through familiarization with the school environment. There were 20 children who researchers observed at the Pembina State Kindergarten school in Gorontalo City who aimed at independence. This research method uses a quantitative descriptive method where the method of collecting is data that is under what is happening in the field, namely in the form of observations. The results of this research show that there are children who do not fully meet several indicators of independence. This can be overcome by creating an environment that supports independence, limiting the use of gadgets, and gradually giving responsibilities according to the child's age so that the child gets used to being independent and confident.